Viral Myocarditis Mimicking ST-Segment Elevation Myocardial Infarction Complicated by Thrombocytopenia and Vasculitic Peripheral Neuropathy - Blerina Asllanaj MD; Eric Chang DO; Anthony Dota MD; Yi McWhorter DO (SAGE Publishing, 2022)
Symptomatic myocarditis is classically featured by a flu-like prodrome, dyspnea on exertion, palpitations, substernal chest pain, and abnormal electrocardiogram (ECG). The clinical diagnosis has often been challenging due to its similarities to acute coronary syndrome. Our case involved a patient who presented with claudication of bilateral lower extremity and ST-segment elevation myocardial infarction (STEMI) in the inferior leads. On cardiac catheterization, nonobstructed coronary arteries with left ventricular ejection fraction (LVEF) of 30% were demonstrated. His clinical presentation was consistent with suspected myocarditis, and he improved with immunosuppression. In addition, his thrombocytopenia and severe symptoms of peripheral neuropathy responded to both immunotherapy and anticoagulation. This case highlights the interplay between history taking, physical examination, and multimodal diagnostic imaging.